2020
DOI: 10.1039/d0ra02842h
|View full text |Cite
|
Sign up to set email alerts
|

Hot electron transfer in Zn–Ag–In–Te nanocrystal–methyl viologen complexes enhanced with higher-energy photon excitation

Abstract: Zn–Ag–In–Te nanocrystals exhibited hot electron transfer to adsorbed methyl viologen, the efficiency being enhanced from 45% to 72% with an increase in the excitation photon energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In other words, a high energy injection accelerates the relaxation process of carriers. A similar result has also been found in quantum dots and 2D films [ 51 , 52 , 53 ].…”
Section: Resultssupporting
confidence: 85%
“…In other words, a high energy injection accelerates the relaxation process of carriers. A similar result has also been found in quantum dots and 2D films [ 51 , 52 , 53 ].…”
Section: Resultssupporting
confidence: 85%
“…Ultimately, the improved efficiency of electron–phonon interaction promotes the cooling process, or in other words, it is high energy injection that speeds up electron decay. Similar properties can be seen in either quantum dots or 2D films [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 52%
“…Moreover, the linear dependence of measured transient signals for both the systems upon excitation intensities in the studied range (5–200 μW ≈ 10 × 10 –9 to 40 × 10 –8 J/pulse) as well as exactly the same kind of decay profiles of all studied excitation intensities confirm the absence of multiexciton generation and Auger recombination processes for both the systems. Okuhata et al reported similar observations, and it was rationalized as the hot electron transfer (HET) from the 1P­(e) state of CdSe QDs to Au in CdSe QD–Au heterostructures and from the Zn–Ag–In–Te nanocrystal to methyl viologen (MV 2+ ) in ZAIT NC–MV 2+ complexes . Note that no difference in transient signal strength of bare CdTe QDs and CdTe QD–TCPP 1 NCs at initial delays is observed along with no change in rise time of the 1S bleach signal when both systems were excited in the vicinity of 1S exciton absorption (see Supporting Information for more, Figure S7–S11), which again ensures that there is no electron transfer from the band-edge exciton (1S) to TCPP in CdTe QD–TCPP 1 NCs.…”
Section: Resultsmentioning
confidence: 71%